Up and over - a vision of perseverance - Marrazzo, Mesina (My University, 2022)
The hot air balloon is a vision of perseverance, strength, and freedom. Combined with the sunrise's mystery of what a new day might bring, this album package compels the viewer to think and wonder, just as the music of the Up and Over Trio desires to incite thoughtful introspection. The name Up and Over has grown to represent the Trio’s resilience through the challenges of freelance and side jobs, finally coming together to create their first album. The sunrise indicates this new beginning, while the hot air balloon serves as a visual representation of rising up and over. Across the package, images of balloons drifting across a muted sunrise lend themselves to a compelling experience of deliverance and tenacity. The progress to a sky of blue, so as the viewer opens the package, they are guided from the bright orange sunrise on the cover to a soft morning glow that follows soon after. The record’s centre labels bring the viewer to the cornerstone of their journey: when they look up during their ride through the clouds and the rising sun to behold the very thing controlling their rise and fall — a flap at the top of the balloon that releases hot air. This little hole dictating rise and fall is controlled by a simple cord within the pilot’s grasp. On a journey through the hardships and challenges of life, everyone stands at the helm of their ship with the power to fall down or rise up and over.
Presented on April 21, 2022 at Student Research Day at MacEwan University in Edmonton, Alberta.
Keywords: package design; album covers